A novel and feasible mouse model of modified inoculation method by subcutaneous EMT6 cells injection for subclinical breast cancer. Issue 3 (September 2022) - Pan, Lingxiao; Huang, Zizhong; Li, Guangqiu; Zhan, Qianchao; Zheng, Wenbo; Chen, Lun; Zhang, Xiaoshen
Abstract: To create a subclinical breast cancer mouse model. Using a modified inoculation method, we injected EMT6 cells subcutaneously into the bilateral 4th mammary fat pads of six BALB/c mice. The mice were then bilaterally inoculated with various cell numbers. Each group underwent unilateral resection of the 4th nipple and mammary fat pad at a 24-h interval. The modified subcutaneous inoculation method was simple, safe, and demonstrated good consistency in bilateral tumor growth rates during the early stages of tumor formation. The physical differences in the physical characteristics of the bilateral tumors ranged from 75% to 120% for each mouse. Additionally, by varying the number of injected cells, the times for forming solid tumors of approximately 5 mm in maximum length were 5–6 days (0.5 × 10 6 EMT6 cells) and 6–8 days (1 × 10 6 EMT6 cells) after injection, and the difference was statistical significant ( P  = 0.008); for these models, the ideal time points representing subclinical stages were 24 h and 72 h after inoculation, respectively. Our findings show that the optimal time point for isolating the subclinical stage of breast cancer differs depending on the number of EMT6 cells injected into the 4th mammary fat pad of BALB/c mice.